ACTR-38. A PHASE I TRIAL OF AFATINIB AND RADIOTHERAPY (RT) WITH OR WITHOUT TEMOZOLOMIDE (TMZ) IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA (GBM). (5th November 2018) - Saran, Frank; James, Allan; McBain, Catherine; Jefferies, Sarah; Harris, Fiona; Cseh, Agnieszka; Pemberton, Karine; Schaible, Jennifer; Bender, Shaun; Brada, Michael
Abstract: GBM is the most frequent primary CNS tumor. RT + TMZ represents first-line therapy. ErbB pathway dysregulation contributes to GBM pathogenesis; EGFR activation is associated with RT resistance. This 3 + 3 dose-escalation study assessed afatinib, an irreversible ErbB family blocker, with RT ± TMZ in newly diagnosed GBM. Patients with MGMT promoter methylation received afatinib (20, 30, 40 mg/day) + RT + TMZ for 6 weeks (RT period), then afatinib 40 mg/day + TMZ for 6 months, then afatinib 40 mg/day until progression/undue adverse events (AEs; Regimen M). Those with unmethylated MGMT promoter received RT + afatinib then afatinib (Regimen U). Primary endpoint was maximum tolerated dose (MTD) of afatinib + RT ± TMZ; secondary endpoints were safety, pharmacokinetics and antitumor activity. Thirty-six patients were enrolled (M, 20; U, 16). In regimen M, 1/6 (20 mg), 0/6 (30 mg) and 2/5 (40 mg) evaluable patients had dose-limiting toxicities (DLTs) in the RT period (two Grade 4 thrombocytopenia, one Grade 3 vomiting); MTD of afatinib + RT + TMZ was 30 mg/day. In regimen U, 0/3 (20 mg) and 1/6 (40 mg) evaluable patients had DLTs (Grade 3 diarrhea); MTD of afatinib + RT was 40 mg/day. Common treatment-related AEs were diarrhea, rash, fatigue, nausea and thrombocytopenia; 80% and 75% had Grade 3 AEs in M and U. Pharmacokinetic evaluation suggested that afatinib with RT ± TMZ had no influence on afatinib exposure. Five patients in M and one in U had an objective response. Five patients (M, 4; U, 1) were long-term responders to afatinib (>12 months treatment); two had available tumor samples. Both had MGMT promoter methylation; one had a PTPN11 mutation, the other focal EGFR amplification with concomitant EGFRvIII allele amplification. Afatinib + RT ± TMZ appears tolerable; preliminary biomarker analysis may indicate patients likely to have long-term responses.